Taking Stock of Accounting Ethics Scholarship: A Review of the Journal Literature - Bampton, Roberta (Journal of business ethics, 2013)
The proportion of business ethics literature devoted to accounting and the proportion of academic accounting literature devoted to ethical issues are both small, yet over the past two decades there has been a steady accumulation of research devoted to ethical issues in accounting. Based on a database of more than 500 articles gathered from a wide range of accounting and business ethics academic journals, this paper describes and analyses the characteristics of what has been published in the past 20 years or so. It identifies and explores patterns and trends in publication outlets and the type of research conducted. Furthermore, through a comparison with issues that have been raised in the general business ethics literature, it offers guidance to researchers who intend to take the field of accounting ethics forward using empirical methods.